2023
DOI: 10.1039/d3gc00703k
|View full text |Cite
|
Sign up to set email alerts
|

Molecular understanding of the morphology and properties of lignin nanoparticles: unravelling the potential for tailored applications

Abstract: Studies have shown that the size of LNP depends on the molecular weight (Mw) of lignin. There is however need for deeper understanding on the role of molecular structure on...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 49 publications
0
4
1
Order By: Relevance
“…3a and b). Previous studies reported that smaller LNPs were successfully prepared with higher molar mass lignin [30,42]. However, those statement is not consistent with the results of this study.…”
Section: Carbohydrate Content and Molar Mass Of Lignin-based Fraction...contrasting
confidence: 99%
“…3a and b). Previous studies reported that smaller LNPs were successfully prepared with higher molar mass lignin [30,42]. However, those statement is not consistent with the results of this study.…”
Section: Carbohydrate Content and Molar Mass Of Lignin-based Fraction...contrasting
confidence: 99%
“…Previous studies have indicated that the self-assembly of lignin compounds is driven by hydrogen bonding, π–π interactions among aromatic groups within and between molecules, and hydrophobic interactions. 58,59 As the water content in the system increased, the polar segment of formic acid lignin compounds exhibited an affinity for water, leading to an escalation in the polar group content (carboxyl, hydroxyl). Conversely, the water molecules around the non-polar hydrophobic skeleton were excluded and repelled, therefore stabilizing the contact of non-polar regions.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, there are some cases where hemicelluloses can stabilize lignin particles. , This stabilization of LNPs by attached polysaccharide chains is due to increased osmotic pressure when the particles approach each other, as the concentration of polysaccharide segments locally increases, causing a repulsive force. Recently, DFT calculations also support that the molecular structure of lignin strongly influences the formation of LNPs, so that flexible interunit linkages, specifically the β-O-4′ substructures, yield molecular folding resulting in intramolecular π–π stacking which presumably supports the assembly process …”
Section: Introductionmentioning
confidence: 97%
“…Recently, DFT calculations also support that the molecular structure of lignin strongly influences the formation of LNPs, so that flexible interunit linkages, specifically the β-O-4′ substructures, yield molecular folding resulting in intramolecular π–π stacking which presumably supports the assembly process. 19 …”
Section: Introductionmentioning
confidence: 99%